Determinants of Exchange Market Pressure in Turkey: An Econometric Investigation - Feridun, Mete (M E Sharpe Inc, 2009)
This paper investigates the hypothesis that there is a causal relation between speculative pressure and real exchange rate overvaluation, banking-sector fragility, and the level of international reserves in Turkey. An autoregressive distributed lag (ARDL) bounds-testing procedure and Granger causality within vector error-correction models (VECM) are applied to the period after the liberalization of capital flows (August 1989-August 2006). The results of the ARDL bounds test support the theory that exchange market pressure is in a long-run equilibrium relation with the three hypothesized variables over the sample period. On the other hand, the results of the short-run and long-run Granger causality tests indicate the existence of Granger causality running from the three variables to exchange market pressure. The findings further suggest that a feedback relation exists between banking-sector fragility and exchange market pressure.
Keywords: ARDL bounds test; exchange market pressure; Granger causality